Inkjet-printed electronics for rapid and low-cost prototyping of digital microfluidic devices using an off-the-shelf printer - Babak Kamali Doust Azad; Amirhossein Roozbahani; Seyed Mohammad Tabatabaei; Amirali Valinejad; Alireza Fazelian; Kimia Shahmoradi; Fatemeh Khatami; Seyed Mohammad Kazem Aghamir; Mohammadreza Kolahdouz (Scientific Reports)
Abstract Digital microfluidics (DMF) is revolutionizing point-of-care diagnostics by advancing lab-on-a-chip technology. To accelerate translation to real-life applications, it is crucial to devise rapid and low-cost methods for prototyping to test various design ideas. Here, we present one such method using an unmodified desktop inkjet printer and inexpensive materials. Inkjet-printing eliminates the need for costly printed circuit board technology or microfabrication facilities, significantly lowering the barriers to entry for researchers in the field of DMF technology. Here, an inkjet printer is characterized to print conductive tracks of Ag-ink on polyethylene terephthalate (PET) and glass slide substrates, delivering a maximum surface conductance of 7.69 Ω−1/cm2. Functional DMF chips are fabricated using tape, parafilm, and SU8 as dielectric and silicone oil as the hydrophobic layers, enabling actuation voltages as low as 144 VDC and 92 VAC@100 kHz for a whole-blood droplet. We detail our actuation and control circuitry, designed entirely with standard electronic modules and components. To showcase our approach, we fabricated a DMF micromixer and assessed its performance using image processing, proving the quality of the mixing. Leveraging affordable inkjet printing, our approach paves the way for highly accessible research and development in DMF-based point-of-care diagnostics.